1988
DOI: 10.1007/bf00006967
|View full text |Cite
|
Sign up to set email alerts
|

Food resource utilization partitioning of fifteen fish species at Bukit Merah Reservoir, Malaysia

Abstract: Statistical and mathematical models have been used to measure the subtle differences in food resources utilisation of fifteen (15) fish species at Bukit Merah Reservoir, Malaysia. The models employed are niche breadth, dietary overlap indices and discriminant analysis. A diet measure based on the relative importance index of food items was used for the analysis, to correct for biases of the single indices consisting of the volumetric, numerical and occurrence frequency. Niche breadth (B,) indicating the divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 20 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…Poropuntiini are mostly recognized as omnivorous, with some species preferentially feeding on plant matter, for example Puntioplites, and others on animal matter (insects, crustaceans or even fish), for example Cyclocheilichthys [31,32]. Labeonini are mostly reported as phytophagous and microphagous, mostly feeding on algae, periphyton, phytoplankton and, in lesser proportion, zooplankton [30][31][32]. By exploiting the whole benthopelagic zone, Poropuntiini thus display a wider range of food habits than Labeonini.…”
Section: (D) Dietmentioning
confidence: 99%
“…Poropuntiini are mostly recognized as omnivorous, with some species preferentially feeding on plant matter, for example Puntioplites, and others on animal matter (insects, crustaceans or even fish), for example Cyclocheilichthys [31,32]. Labeonini are mostly reported as phytophagous and microphagous, mostly feeding on algae, periphyton, phytoplankton and, in lesser proportion, zooplankton [30][31][32]. By exploiting the whole benthopelagic zone, Poropuntiini thus display a wider range of food habits than Labeonini.…”
Section: (D) Dietmentioning
confidence: 99%
“…Liem (1984) states that many teleosts, including cichlid fishes, show a high degree of flexibility in the use of the buccal apparatus and are able to exploit more than one food source, which enables the exploitation of broader and more overlapping niches than, for instance, terrestrial tetrapods. This hypothesis is supported by studies which show a high degree of overlap in diet between fishes belonging to the same community (Hynes, 1950;Fuller & Hynes, 1987;Siaw-Yang, 1988;Bolger et al, 1990;Urban & Brandt, 1993). More detailed studies have shown that often a very subtle niche differentiation exists between coexisting species that were once thought to occupy the same trophic niche (Gladfelter & Johnson, 1983;Goldschmidt et al, 1990;Yamaoka, 1991).…”
Section: Introductionmentioning
confidence: 91%
“…Barbonymus schwanenfeldii is native to the Mekong and Chao Phraya basins (Cambodia, Laos, Thailand and Vietnam), the Malay Peninsula, Borneo and Sumatra (Kottelat, 2001). It is a schooling species growing up to 340 mm standard length ( L S ) (Kottelat, 2001) with an omnivorous and detritivorous habit, feeding on aquatic and terrestrial macrophytes, filamentous algae, small fishes and occasionally insects (Siaw‐Yang, 1988; Rainboth, 1996). It is a highly fecund species with females producing 7900–16 000 eggs for fish weighing 220–382 g (Christensen, 1992) and a spawning frequency of three times per year in a regulated river (McAdam et al , 1999).…”
Section: Meristic Characters Of Two Barbonymus Schwanenfeldii Specimementioning
confidence: 99%